Sound and Fury. Lending an Ear to Francis Bacon in The Shout (dir. Jerzy Skolimowski, 1978, uk) - Chare, Nicholas (Revue musicale OICRM, 2023)
The Shout (1978), directed by Jerzy Skolimowski, is a horror film that centres upon a man, Charles Crossley, capable of executing a shout so intense that its effects overwhelm those who hear it. As the film’s title suggests, acoustic phenomena are central to the narrative. Another key protagonist, Anthony Fielding, is an avant-garde composer. He experiments with various noises as he makes works of musique concrète. Photographic reproductions of paintings by Francis Bacon are displayed in Fielding’s recording studio and, on one level, symbolize his sources of inspiration. Bacon’s works, however, also inform the mise-en-scène of The Shout, comprising part of the fabric of the film. They are not simple props. In this essay, I will argue that the film’s aesthetic, including its soundtrack and mise-en-scène, should be understood as a form of art writing that imitates elements of Bacon’s aesthetic, an aesthetic I argue is queer and rooted in the artist’s interest in bdsm.